Perancangan Penerapan Manajemen Risiko - Yuha Nadhirah Qintharah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2019)
This research is using ISO 31000:2009 as the standard to build the risk management of UMKM Saripakuan. UMKM Saripakuan has main production in Cookies Production. UMKM Saripakuan has many risks that lists in their production because it has young age. So, this UMKM need designing and implementation of risk management to minimalize those risk. Risk management made so level of those risks in UMKM Saripakuan may reduce into acceptable area so, they can reach their objective optimally. Result of this research shows that UMKM Saripakuan has 14 risks inside UMKM Saripakuan